Si Parcoursup m’était compté - Pauline Boyer; Julien Gossa (Éducation et Socialisation)
This study proposes to evaluate the implementation of the platform Parcoursup, which was introduced by the ORE law in 2018, through the exploitation of open data made available by the Ministry of Higher Education. By examining both official indicators and measures made possible by these data, we aim to shed light on post-secondary orientation public policy. This attempt is made difficult by partial data with unequal reliability and, above all, complex to interpret. This work opens perspectives on their consolidation and the design of national indicators allowing for a better understanding of post-secondary orientation public policy.